Solid waste indicators and their implications for management practice - Deus, R. M. [UNESP]; Bezerra, B. S. [UNESP]; Battistelle, R. A.G. [UNESP] (Springer Nature, 2019)
This study analyzed, through bibliometrics, state-of-the-art municipal solid waste indicators by consulting key articles on the subject from prominent authors and institutions. A content analysis was used to identify main indicators for municipal solid waste performance along with their corresponding sustainability dimensions and implications for the practice of its management. The environmental dimension is the most significant, followed by the economic and social dimensions, because it was found in more papers along time. Emphasis is given to the following indicators related to life cycle: energy indicators (also analyzed with emergy tools); landfill volume or percentage of waste sent to it; waste generation; and rates of composting, recycling, and incineration (may involve the rate of separation at the source). Indicators categorized by the economic dimension are primarily understood by their direct relation to the costs of municipal solid waste management systems, as implementation, maintenance, and operation. Concerning the social dimension, indicators are incipient and present in fewer studies. Among the indicators of this dimension, collection coverages and services (including quantity, types, and rates) are more frequently featured in publications. It is important to highlight that municipal solid waste indicators should be comparable across countries and cities and that international standards for quality management in companies must be established. These standards should be easy to interpret and apply and should include all dimensions of sustainability.
Keywords: Content analysis; Decision-making support; Municipal solid waste; Performance indicators; Sustainability